Genomic landscape of the OsTPP7 gene in its haplotype diversity and association with anaerobic germination tolerance in rice - Aung, Kyaw Myo; Oo, Win Htet; Maung, Thant Zin; Min, Myeong-Hyeon; Somsri, Aueangporn; Nam, Jungrye; Kim, Kyu-Won; Nawade, Bhagwat; Lee, Chang-Yong; Chu, Sang-Ho; Park, Yong-Jin (Frontiers in Plant Science, 2023)
Early season flooding is a major constraint in direct-seeded rice, as rice genotypes vary in their coleoptile length during anoxia. Trehalose-6-phosphate phosphatase 7 (OsTPP7, Os09g0369400) has been identified as the genetic determinant for anaerobic germination (AG) and coleoptile elongation during flooding. We evaluated the coleoptile length of a diverse rice panel under normal and flooded conditions and investigated the Korean rice collection of 475 accessions to understand its genetic variation, population genetics, evolutionary relationships, and haplotypes in the OsTPP7 gene. Most accessions displayed enhanced flooded coleoptile lengths, with the temperate japonica ecotype exhibiting the highest average values for normal and flooded conditions. Positive Tajima's D values in indica, admixture, and tropical japonica ecotypes suggested balancing selection or population expansion. Haplotype analysis revealed 18 haplotypes, with three in cultivated accessions, 13 in the wild type, and two in both. Hap_1 was found mostly in japonica, while Hap-2 and Hap_3 were more prevalent in indica accessions. Further phenotypic performance of major haplotypes showed significant differences in flooded coleoptile length, flooding tolerance index, and shoot length between Hap_1 and Hap_2/3. These findings could be valuable for future selective rice breeding and the development of efficient haplotype-based breeding strategies for improving flood tolerance.